The impact of project-based learning on pediatric nursing education: an integrative review. - Koo, Hyun Young; Lee, Bo Ryeong (Child Health Nursing Research, 2026)
Purpose: This integrative review aimed to examine the application and outcomes of project-based learning (PjBL) in pediatric nursing education and to identify its key characteristics. Methods: Following the integrative review methodology proposed by Whittemore and Knafl, a comprehensive literature search was conducted in May 2025 across PubMed, Embase, CENTRAL, CINAHL, KCI, RISS, ProQuest, and Google Scholar. Studies published in both English and Korean were included. Two reviewers independently screened and selected eligible studies addressing the use of PjBL in pediatric nursing education. Results: Six studies met the inclusion criteria and were included in the final review. Learning outcomes were categorized into 3 domains: cognitive outcomes (improvements in knowledge and critical thinking), affective-attitudinal outcomes (reduced stress and enhanced positive attitudes and self-confidence), and psychomotor outcomes (improvements in performance skills). The role of faculty members as facilitators, supporters, and coordinators emerged as a key determinant of successful PjBL implementation. PjBL may provide beneficial learning outcomes across multiple domains in pediatric nursing education; however, the overall level of evidence ranged from low to moderate, and the findings should therefore be interpreted with caution. Conclusion: For successful implementation, faculty play a critical role in guiding and supporting the learning process. Accordingly, PjBL should be more widely incorporated into nursing curricula, accompanied by adequate faculty development initiatives.